Returns to Education in the Russian Federation : Variation Across Regions and Implications for Policy Development in Priority Regions - Melianova, Ekaterina; Parandekar, Suhas; Volgin, Artem (World Bank, Washington, DC, 2020)
This paper uses regionally representative household survey data to determine the rates of return to education in different regions. Returns show a wide dispersion together with the labor market context. The paper’s policy recommendations will be particularly helpful to support human capital development of federally targeted economically and socially depressed regions.